OPTIMALISASI BAHAN AJAR BUKU CERITA RAKYAT TERHADAP NILAI-NILAI MORAL PADA BACAAN BAHASA INDONESIA KELAS IV SEKOLAH DASAR SANGGAR BIMBINGAN MUHAMMADIYAH KEPONG - Rismauli; Dewi Kesuma Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to optimize the use of folktale books in teaching Indonesian language to fourth-grade students at SD Sanggar Bimbingan Muhammadiyah Kepong, Kuala Lumpur, Malaysia, in order to improve reading comprehension while instilling moral values. The research employs a Classroom Action Research (CAR) design based on the Kemmis and McTaggart (1988) model, conducted in two cycles consisting of planning, action implementation, observation, and reflection. The subjects of this study were nine fourth-grade students, observed through classroom observation, interviews, and reading comprehension tests, with data analyzed qualitatively and quantitatively. The results indicate a significant improvement from Cycle I to Cycle II. In Cycle I, the average reading comprehension score was 68 with a mastery level of 55.5%, while moral value comprehension reached an average of 70 with 60% mastery. After refining the learning strategies in Cycle II, the average reading comprehension score increased to 82 with 88.8% mastery, and moral value comprehension improved to 85 with 91.1% mastery. Qualitative analysis revealed that students became more active in reading, discussing, expressing opinions, and were able to identify and internalize moral messages from the stories. Based on these findings, it can be concluded that folktale books are effective teaching materials for enhancing reading comprehension and moral value development among fourth-grade students. This story-based learning strategy not only supports cognitive learning outcomes but also fosters positive character development, reading interest, critical thinking skills, and moral awareness. These findings can serve as a reference for teachers in designing more interactive, meaningful, and character-based Indonesian language learning activities.